2015
DOI: 10.1021/acs.jchemed.5b00209
|View full text |Cite
|
Sign up to set email alerts
|

Impact of General Chemistry on Student Achievement and Progression to Subsequent Chemistry Courses: A Regression Discontinuity Analysis

Abstract: General chemistry is a gateway course that impacts the STEM trajectory of tens of thousands of students each year, and its role in the introductory curriculum as well as its pedagogical design are the center of an ongoing debate. To investigate the role of general chemistry in the curriculum, we report the results of a posthoc analysis of 10 years of archived student data (ca. 12,000 students) aimed at discovering whether taking college-level general chemistry has an impact on student performance in and progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 38 publications
(66 reference statements)
1
19
1
Order By: Relevance
“…It should also be noted that the group that has the lowest average grade and passing rate is the one where the students are taking the course again. These results align partially with previous results from Shultz et al, who found that general chemistry had a statistically significant positive impact on subsequent organic chemistry grades, but the general chemistry impact on the pass rate in organic chemistry was not statistically significant …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…It should also be noted that the group that has the lowest average grade and passing rate is the one where the students are taking the course again. These results align partially with previous results from Shultz et al, who found that general chemistry had a statistically significant positive impact on subsequent organic chemistry grades, but the general chemistry impact on the pass rate in organic chemistry was not statistically significant …”
Section: Resultssupporting
confidence: 86%
“…These results align partially with previous results from Shultz et al, who found that general chemistry had a statistically significant positive impact on subsequent organic chemistry grades, but the general chemistry impact on the pass rate in organic chemistry was not statistically significant. 19 When the grades from general chemistry and organic chemistry are compared, a moderately strong correlation is observed, r = 0.71 and r = 0.66, respectively, for groups 1 and 2. The correlation coefficient is very similar for both groups, however, so limited conclusions should be drawn from these results alone.…”
Section: Resultsmentioning
confidence: 97%
“…For example, one project revealed that first-year engineering students who received a 4 on their Math AB Advanced Placement (AP) exam only received an A or B grade 50% of the time when enrolling in Calculus II their first term (Nam, Lonn, Brown, Davis, & Koch, 2014). A different project analyzed the impact of a general chemistry prerequisite on later student achievement and progression in subsequent chemistry courses (Shultz, Winschel, & Gottfried, 2015). A significant number of these projects each independently obtained, transformed, and analyzed institutional student data, replicating such work for each subsequent project.…”
Section: Institutional Context and Rationalementioning
confidence: 99%
“…For example, three of the fellows from the Chemistry Department (Shultz, Winschel, & Gottfried, 2015) analyzed the impact of a general chemistry prerequisite on later student achievement and progression in subsequent chemistry courses. The syllabus for this initial cohort included an introduction to institutional data sets, course recommender systems, data visualization, course-level data, noncognitive factors, the institutional review board (IRB) and the Family Educational Rights and Privacy Act (FERPA), and data ethics and privacy.…”
Section: The Learning Analytics Fellows Programmentioning
confidence: 99%
“…Many of the fellows in this initial class used the funds to support their initial research ideas or later submitted proposals for ELA grants and other national grants. For example, three of the fellows from the Chemistry Department (Shultz, Winschel, & Gottfried, 2015) analyzed the impact of a general chemistry prerequisite on later student achievement and progression in subsequent chemistry courses.…”
Section: The Learning Analytics Fellows Programmentioning
confidence: 99%